VISCOELASTIC ASSISTED DRAINAGE OF SUPRACHOROIDAL HEMORRHAGE ASSOCIATED WITH SETON DEVICE IN GLAUCOMA FILTERING SURGERY. Issue 2 (February 2017) - Kurup, Shree K.; McClintic, Jedediah I.; Allen, John C.; Baartman, Brandon J.; Altaweel, Michael M.; Garg, Sunir J.; Quiroz-Mercado, Hugo
Abstract : Purpose: The purpose of this article is to describe a novel surgical technique for the management of large suprachoroidal hemorrhages associated with the insertion of glaucoma seton devices. Methods: In this interventional case series, the authors describe six eyes of six patients who had management of suprachoroidal hemorrhage with pars plana choroidal drainage along with simultaneous insertion of viscoelastic into the posterior segment. All patients had a median of 8-month postoperative follow-up. Results: Five of the 6 patients had useful final vision ranging from 20/40 to 20/200. In all cases, the postoperative intraocular pressures did not increase beyond 28 mmHg and responded to aqueous humor suppressants. Conclusion: As suprachoroidal hemorrhage can be a devastating complication of glaucoma surgery, the authors report a relatively straightforward surgical technique that can restore ambulatory vision in a high proportion of patients. Abstract : Supplemental Digital Content is Available in the Text.Five of 6 patients managed with viscoelastic drainage of suprachoroidal hemorrhage associated with insertion of a glaucoma seton filtering device had visual outcomes of 20/200 or better at 8-month follow-up.